Sistem Informasi Pengajuan Proposal Tugas Akhir Berbasis Web dengan RBAC Multi-Tenant dan Deteksi Kemiripan Judul Menggunakan Metode Agile Scrum - duandi; Ilwan Syafrinal (Journal of Digital Ecosystem for Natural Sustainability, 2026)
The submission and evaluation of final project proposals constitute a vital administrative stage in higher education. At Universitas Universal, this process previously relied on semi-manual methods via Google Drive and spreadsheets, which led to data privacy vulnerabilities, examiner evaluation bias, and inefficient data recapitulation. To address these challenges, this study developed a centralized, web-based proposal submission and monitoring information system. Built using Laravel and MySQL databases, the software development process was managed through the Agile Scrum framework across four Sprints. The system incorporates Role-Based Access Control (RBAC) to enforce multi-tenant document security, an asynchronous similarity check using a recursive common substring match to prevent title duplication, and an independent grading module using digital rubrics to ensure objectivity. Software quality evaluations demonstrated high reliability: functional black-box testing achieved a 100% success rate, PHPUnit testing (183 test cases, 611 assertions) passed without errors, and white-box testing showed an overall statement code coverage of 76.9% (exceeding 87% in critical business logic and database model layers). The system successfully digitizes, secures, and standardizes the academic proposal workflow. Keyword: Proposal Submission, Agile Scrum, Role-Based Access Control, Independent Assessment, Digital Rubric